Enhancing Malay essay writing through scaffolding: a pedagogical approach - Mohd Noor, Nur Atikah; Mahamod, Zamri; Nasri, Nurfaradilla Mohamad (Journal of Education and Learning (EduLearn), 2025)
Essay writing is crucial for students as it fosters effective communication and improves critical and analytical thinking. This study investigates the impact of scaffolding techniques on Malay language essay writing proficiency among year 5 students in Malaysia. Based on Vygotsky’s socio-cultural theory, scaffolding offers structured support that gradually disappears as students gain proficiency. A quasi-experimental design was employed, comparing an experimental group using scaffolding methods with a control group following traditional teaching. Results revealed that scaffolding significantly improved students’ essay length, coherence, and overall content quality. The experimental group demonstrated higher scores and greater independence in writing. These findings support the integration of scaffolding in essay instruction to enhance student performance and autonomy in writing. Further research should explore its applicability across diverse age groups and contexts.